Mobile Simulation Contributions to Healthcare Professionals and the Community: Scoping Protocol Review - Silva, Cristiane Costa Reis da (2020)
The purpose of this Scoping Review is to identify and analyze in the literature the use of the mobile simulation strategy for health professionals and the community. Clinical simulation is a form of active methodology that safely favors the development of various skills and competencies for both students and health professionals, helps decision making by allowing the simulated situation to be repeated without exposing the patient to mistakes. Mobile simulation is a recent field of clinical simulation and refers to the simulation that is transferred to professionals. The question that guides this review is: what contributions from mobile simulation have been identified and evaluated in the training processes of health professionals and the community? The methodological route used for the development of this protocol followed the guidelines of the Joanna Briggs Institute for scoping review, consisting of five steps: formulation of the research question; identification of relevant studies; Selection of studies; mapping of scientific evidence; presentation and interpretation of results.